Community ‘de-addiction’ camps: A follow-up study - Raj, Lok (Medknow Publications, 2005)
AIM: To evaluate the effectiveness of the camp approach for the treatment of alcohol and drug dependence. METHODS: This was a prospective, longitudinal study with a 6-month follow-up. Patients were drawn from the villages covered under the community outreach programme of the Department of Psychiatry of the Government Medical College and Hospital, Chandigarh. Forty-six patients with a history of substance use (alcohol: 23, opioids: 20, cannabis: 2, sedative/hypnotic: 1) admitted to two different community camps for 10 days each were followed up in the community outreach clinics of the respective villages. Sociodemographic and clinical variables were recorded on a semi-structured proforma. Outcome variables, changes in dose, frequency, route of intake, status of complications, etc. were recorded on a specially designed semi-structured proforma at the end of 6 months of treatment. The ICD-10 criteria were used for diagnoses. RESULTS: Thirty-six patients (78.3%) completed 6 months' follow-up, 61% recovered totally or their condition improved markedly. There were significant improvements in physical health and family life. CONCLUSION: The camp approach is a cheap and effective treatment alternative for patients with alcohol and drug dependence.